2012
DOI: 10.2478/v10213-012-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Proinflammatory Mediators of The Arachidonic Acid Cascade in Serum of Sheep with Natural Zearalenone Intoxication

Abstract: The clinical form of natural zearalenone intoxication was observed in sheep that were kept indoors and fed a constant diet of feed concentrates containing high concentrations of zearalenone and its metabolite α-zearalenol. The clinical form of the disease was not noted in the control group, consisting of sheep that were kept on a pasture from spring to late autumn; only in the winter they were fed wheat pellets, in which the zearalenone concentration was determined to be the lowest among all used feed concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The systemic bioavailability of ZEN was reviewed to vary between 78 and 87% suggesting that just 22 to 13% of an oral bolus are excreted via feces and the rest gets in contact with immune cells ( 55 ). Studies have reported maximal plasma concentrations up to 15 µg/mL (47 µM) ZEN after oral ingestion of ZEN via feed ( 56 ). The metabolites DOM-1 and HZEN were tested in equivalent, but physiological not relevant concentrations, to example the non-toxic effects thereof.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic bioavailability of ZEN was reviewed to vary between 78 and 87% suggesting that just 22 to 13% of an oral bolus are excreted via feces and the rest gets in contact with immune cells ( 55 ). Studies have reported maximal plasma concentrations up to 15 µg/mL (47 µM) ZEN after oral ingestion of ZEN via feed ( 56 ). The metabolites DOM-1 and HZEN were tested in equivalent, but physiological not relevant concentrations, to example the non-toxic effects thereof.…”
Section: Discussionmentioning
confidence: 99%
“…[ 61 ] In addition, the proteomic analysis conducted on human macrophages showed as the emerging mycotoxin alternariol (1 µM for 3 h) caused immune toxicity, by increasing the production of eicosanoids such as 12‐HETE, which enhanced the transcription of proinflammatory mediators. [ 62 ] Kostro et al [ 63 ] also demonstrated that zearalenone‐induced mycotoxicosis in sheep (3.07–14.49 µg kg −1 for 70 days) was mediated by eicosanoids, which fostered the infiltration of neutrophils in the digestive tract and the onset of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%